A Mutant of 3T3 Cells with Cyclic AMP Metabolism Sensitive to Temperature Change - Willingham, Mark C. (1973)
A mutant line of 3T3 (mouse fibroblast) cells with temperature-sensitive cyclic AMP (cAMP) metabolism was isolated by selecting for low substratum adhesiveness after a change in temperature. Although the mutant is identical in behavior to the parent cell at constant temperature, a rise or fall in temperature causes a fall in intracellular cAMP levels within seconds, followed by loss of adherence to the culture dish and retraction of cell processes. The mechanism of this fall in cAMP level is at least in part excretion into the medium. The decrease in adhesiveness and retraction of processes can be blocked by analogues of cAMP or agents that elevate intracellular cAMP. The properties of this mutant imply that cAMP is a direct regulator of cell shape and adhesiveness.